Implementasi Program Perpustakaan “KEREN” di Kelurahan Air Putih Kota Pekanbaru - Walfikri Walfikri; Zulkarnaini Zulkarnaini (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Community empowerment is a main pillar in the development of a region. Increasing public participation and services is crucial for achieving inclusive and sustainable development goals. Amid the dynamics of modern society, the role of subdistrict libraries in enhancing public services and community participation is increasingly emphasized. According to UNESCO data, the reading interest of Indonesians is very concerning, at only 0.001%. This means that out of 1,000 Indonesians, only one person regularly reads. A different study titled